2018
DOI: 10.1073/pnas.1817239116
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants driving homoserine lactone ligand selection in the Pseudomonas aeruginosa LasR quorum-sensing receptor

Abstract: Quorum sensing is a cell-cell communication process that bacteria use to orchestrate group behaviors. Quorum sensing is mediated by signal molecules called autoinducers. Autoinducers are often structurally similar, raising questions concerning how bacteria distinguish among them. Here, we use the Pseudomonas aeruginosa LasR quorum-sensing receptor to explore signal discrimination. The cognate autoinducer, 3OC 12 homoserine lactone (3OC 12 HSL), is a more potent activator of LasR than other homoserine lactones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 58 publications
6
99
0
1
Order By: Relevance
“…Here, it is noteworthy to mention that docking results revealed butein was able to form H-bond with carbonyl oxygen of Tyr 47. McCready et al, 2018, reported that Tyr 47 present in loop L3 of LasR is able to adopt multiple conformations and hence it can accommodate the different ligands [23]. When LasR Tyr 47 was mutated with other amino acids such as Ser and Arg, the sensitivity to towards AHLs was found to be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is noteworthy to mention that docking results revealed butein was able to form H-bond with carbonyl oxygen of Tyr 47. McCready et al, 2018, reported that Tyr 47 present in loop L3 of LasR is able to adopt multiple conformations and hence it can accommodate the different ligands [23]. When LasR Tyr 47 was mutated with other amino acids such as Ser and Arg, the sensitivity to towards AHLs was found to be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from both of these cases, VqmA binds to either DPO or Ala-AA, but not both, to induce maximal transcriptional activity. This result is curious to us given that QS receptors typically maintain signaling fidelity by distinguishing between different ligands (30)(31)(32)(33). This situation appears analogous to that of the V. cholerae AI called CAI-1 ((S)-3hydroxytridecan-4-one) and its biosynthetic precursor, Ea-CAI-1 (3-aminotridec-2-en-4-one).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-molecular reclosure was performed as described (10) using Q5 High-Fidelity DNA Polymerase (NEB). QuickChange (Agilent) site directed mutagenesis was performed as described (30) using PfuUltra Polymerase (Agilent). The parent pET15b-vqmA vector (JSS-1057) was constructed by PCR of pET15b-His-vqmA (KPS-0929) with primers JSO-654 x JSO-655, followed by intramolecularreclosure to remove the His-tag.…”
Section: Experimental Procedures Bacterial Strains Plasmids Primersmentioning
confidence: 99%
See 1 more Smart Citation
“…Quorum sensing for cell-density dependent communication among bacteria enables coordinated gene expression 17,18 . Quorum-sensing bacteria produce signaling molecules, such as different types of N-Acyl homoserine lactones (AHLs), with the concentration of released signaling molecules dependent upon bacterial population density [19][20][21] .…”
mentioning
confidence: 99%